Juridical Review of Bawaslu's Authority in Handling Digital Disinformation in Elections in Indonesia - Rizal Al Mugni; Demson Tiopan (Master of Law Program, Ekasakti University, 2026)
This study aims to analyze the authority of the General Election Supervisory Agency (Bawaslu) in handling digital campaign disinformation in elections in Indonesia based on the applicable legal provisions. The research method used is a normative juridical method with a legislative and conceptual approach. The results of the study show that the authority of Bawaslu in supervising digital campaigns has been regulated in Law Number 7 of 2017 concerning General Elections, especially in the aspect of supervision and handling of administrative violations. However, in practice, the handling of digital campaign disinformation does not only involve Bawaslu, but also other agencies according to their respective authorities. Therefore, handling disinformation requires coordination between institutions so that it can run effectively. This research also shows that strengthening the authority of Bawaslu is not interpreted as adding new authority, but as an effort to optimize the implementation of existing authority through strengthening coordination, adaptive supervision mechanisms, and improving preventive functions. Thus, Bawaslu has a strategic role as a supervisor as well as a liaison in supporting the handling of digital campaign disinformation within the applicable legal framework.